At the Heart of the Home: EXPLORING THE CULTURAL ROLES OF INTERIOR PARTITIONS IN SARAWAK RIVER MALAY HOUSES OF THE BROOKE ERA - Mohamad Faizuan, Mat (RDICE, UNIMAS, 2025)
This research introduces the idea of Sarawak Malay interior partitions as "hidden cultural artifacts" that reflect both functional, sociocultural and aesthetic values. By focusing on these often-overlooked elements, the study reveals the intricate role of partitions in daily life and cultural expression, positioning them as vital components of Sarawak’s architectural identity.